2018
DOI: 10.1017/s0950268818001607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three cryptosporidiosis outbreaks in Western Australia: 2003, 2007 and 2011

Abstract: Cryptosporidium is a protozoan parasite that causes the diarrhoeal disease, cryptosporidiosis. Although many species have been identified, the majority of human disease worldwide is caused by two species; Cryptosporidium parvum and Cryptosporidium hominis. In Australia, data from the National Notifiable Diseases Surveillance System (NNDSS) show that cryptosporidiosis outbreaks occur every few years. To better understand the transmission, trends and nature of cryptosporidiosis outbreaks in Western Australia, ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A longitudinal study in Western Australia revealed the predominant C. hominis subtype was IdA15G1, occurring in 45% of cases [33]. This subtype has been associated with Australian outbreaks in 2007 [50], has a higher prevalence in Aboriginal populations [51] and is the predominant subtype in rural areas of Western Australia [39].…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study in Western Australia revealed the predominant C. hominis subtype was IdA15G1, occurring in 45% of cases [33]. This subtype has been associated with Australian outbreaks in 2007 [50], has a higher prevalence in Aboriginal populations [51] and is the predominant subtype in rural areas of Western Australia [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Aboriginal people in Australia have been shown to be mainly infected with C. hominis gp60 IdA15G1, whereas non-Aboriginal people were predominantly infected with the IbA10G2 gp60 genotype (Ng-Hublin et al, 2017). Furthermore, alleles IbA10G2 and IdA15G1 have been found to be the most common C. hominis genotypes involved in waterborne cryptosporidiosis outbreaks in Australia during the period 2007-2011 (Ng-Hublin et al, 2018). As a result of these outbreaks investigations, a clustering of cases with the IdA15G1 gp60 genotype was detected in Aboriginal people living in remote areas, affecting primarily children under 4 years of age.…”
Section: Cryptosporidium Hominis In Wildlife Other Than Primatesmentioning
confidence: 99%
“…Infectious oocysts may live in the atmosphere for a long time and are not harmed by traditional disinfection methods (including chlorination and iodine), so that they may spread easily via water (Guy et al 2021). Outbreaks of human Cryptosporidiosis were reported during 1987, 1993, 2005, 2007, 2008, 2009, 2014 and 2017 in the United States of America (Gharpure et al 2019;Alleyne et al 2020Alleyne et al ), in 1995Alleyne et al , 2005Alleyne et al , 2008 and 2010 in UK (Chalmers et al 2011(Chalmers et al ), in 1996(Chalmers et al and 2001 in Canada (Iqbal et al 2015;Guy et al 2021), in 2002, 2007in Ireland (Thomson et al 2007Mahon and Doyle 2017), in 2003, 2007in Australia (Ng-Hublin et al 2015Ng-Hublin et al 2018 in Sweden (Insulander et al 2013;Bjelkmar et al 2017), in 2020 in New Zealand (Garcia et al 2020(Garcia et al ), in 2006(Garcia et al , 2009(Garcia et al , 2017(Garcia et al and 2019 in France (Costa et al 2020(Costa et al ), in 2001(Costa et al and 2005 in Kuwait (Majeed et al 2018(Majeed et al ), in 2010(Majeed et al , 2014(Majeed et al and 2016 in Pakistan (Raja et al 2014;Khushdil et al 2016), in 2010 and 2014 in India (Sarkar et al 2014) and in 2012 in Malaysia (Rossle et al 2012). Sporadic cases of human Cryptosporidiosis have been reported in Iraq, Jordan, Saudi Arabia, China, Iran and Lebanon (Feng et al 2012;…”
Section: Introductionmentioning
confidence: 99%